A novel mitochondrial DNA deletion in a patient with Pearson syndrome and neonatal diabetes mellitus provides insight into disease etiology, severity and progression. (3rd July 2016) - Chen, Xin-Yu; Zhao, Si-Yu; Wang, Yan; Wang, Dong; Dong, Chang-Hu; Yang, Ying; Wang, Zhi-Hua; Wu, Yuan-Ming
Abstract: Pearson syndrome (PS) is a rare, mitochondrial DNA (mtDNA) deletion disorder mainly affecting hematopoietic system and exocrine pancreas in early infancy, which is characterized by multi-organ involvement, variable manifestations and poor prognosis. Since the clinical complexity and uncertain outcome of PS, the ability to early diagnose and anticipate disease progression is of great clinical importance. We described a patient with severe anemia and hyperglycinemia at birth was diagnosed with neonatal diabetes mellitus, and later with PS. Genetic testing revealed that a novel mtDNA deletion existed in various non-invasive tissues from the patient. The disease course was monitored by mtDNA deletion heteroplasmy and mtDNA/nucleus DNA genome ratio in different tissues and at different time points, showing a potential genotype–phenotype correlation. Our findings suggest that for patient suspected for PS, it may be therapeutically important to first perform detailed mtDNA analysis on non-invasive tissues at the initial diagnosis and during disease progression.